Dimensioning of Excavation-Loading and Transportation Transport Routes at Open-Pit Mining Enterprises (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Information is given about the stages of designing the dimensions of the open-pit mining and loading transport and the initial movement of the transport transport. In this case, the dimensions of the digging-loading and transport vehicles, the distance of movement and the scheme drawings of the movement path are shown as an example. Transportation of overburden and mineral raw materials in surface mining is one of the most complex and expensive operations. today's processes. Good transport routes are essential for successful open pit truck transport. Inadequate road design and maintenance has a major impact on high transport costs and potential hazards. from a security point of view. Numerical modeling was performed to analyze the effect of the installed features materials used in the construction of roads, the thickness of the layers and the interaction of tires with the road surface.